Pengaruh Stress Kerja Dan Kecerdasan Emosional Terhadap Kinerja Karyawan Di Pt Lolc Ventura Indonesia Area Banten - Siti Kuraeni; Styo Budi Utomo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of work stress and emotional intelligence on employee performance at PT LOLC Ventura Indonesia, Banten Area. The research method used is an associative method with a quantitative approach, analyzed both partially and simultaneously. Data were obtained through questionnaires distributed to employees of PT LOLC Ventura Indonesia, Banten Area, and processed using SPSS version 23. Based on the results of the simultaneous hypothesis test (F-test), the calculated F value was 110.464 with a significance value of 0.000. Since the significance value is smaller than 0.05 (0.000 < 0.05), it can be concluded that H₀₃ is rejected and Hₐ₃ is accepted. Thus, the analysis indicates that Work Stress (X₁) and Emotional Intelligence (X₂) simultaneously have a significant effect on Employee Performance (Y) at PT LOLC Ventura Indonesia, Banten Area. The positive regression coefficients of both independent variables indicate that the relationship is positive in direction. Emotional intelligence has a significant effect on employee performance, with a t-value of 10.476 and a significance level of 0.000 < 0.05, contributing 53.3%. Simultaneously, work stress and emotional intelligence have a significant effect on employee performance with an F value of 73.875 and a significance level of 0.000 < 0.05, with a joint contribution of 60.9%. Therefore, it can be concluded that emotional intelligence is the most dominant variable influencing employee performance. The better employees are at managing work stress and the higher their emotional intelligence, the better their performance will be.